Impact of Rapid Tourism Growth on Water Scarcity in Bali, Indonesia - Eva Mia Siska Yamamoto; Takahiro Sayama; Kaoru Takara (Indonesian Journal of Limnology, 2021)
Despite Bali’s dependency on tourism, concerns over the impact of tourism on water scarcity are increasing. The objective of this study is to analyze the clean water demand related to tourism growth and compare them with the available clean water supply. This study suggested that tourism water demand has increased by 20.8 million m3 (295%) from 1988 to 2013. Sixty-eight percent of the increase was concentrated in Badung Regency, where the tourism water demand ratio has increased from 31% to 46%. The study also suggested that rapid population growth has caused an increase in domestic water demand by 48.3 million m3 (48%). This study also shows that the capacity of clean water supply in Bali has increased significantly to meet these demands and the water supply coverage of domestic water demand has increased significantly from 13% in 1988 to 53% in 2013. The water supply coverage of tourism demand varies from year to year with an average of 28% in the study period. The increasing issues over water scarcity despite the improvement in the coverage of domestic water demand suggest further investigations. Yet, despite the large gap between supply and demand in the tourism sector the industry still can have undisrupted clean water throughout the year. This indicates the use of alternative clean water which can be obtained locally such as groundwater. Wise water management through the sharing of scientific data, including in the tourism sector is imperative in solving water scarcity in Bali.  Keywords: clean water demand, water scarcity, Badung Regency